The Effects of Self-Efficacy and Academic Engagement on Academic Resilience - Nisa, Fitri Insi; Eddy Wibowo, Mungin; Mulawarman, Mulawarman (Universitas Negeri Semarang, 2023)
Academic resilience is an individual’s ability to continue his life after experiencing learning difficulties. This study attempted to prove The effects of self-efficacy and academic engagement on academic resilience. It used a correlational design and involved 280 university students who were writing final projects. Findings revealed that both self-efficacy and academic engagement affected the students’ academic resilience improvement. Thus, self-efficacy and academic engagement are urged to be enhanced to support the development of students’ academic resilience.